Factors Influencing Stigma to Lesbian, Gay, Bisexual, and Transgender (LGBT) Among Teenagers at Ngaran Village, Gamping, Sleman, Indonesia - Astuti, Dhesi Ari; Kurniati, Nurul (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2018)
Background: As the part of sexual orientation varieties and gender identities, until now the existence of Lesbian, Gay, Bisexual, and Transgender (LGBT) still becomes a social, theological, and psychological problem. Similar to trauma, low self acceptance, low self esteem, and anxiety, if it is not handled properly, the condition will be getting worse. Aims: The aim of the study is to increase prevention efforts toward growing phenomena of TGBT on teenagers. Methods: This is a quantitative study with one group pretest and posttest design. The work involved a total of 41 teenagers at at Ngaran Village, Balecatur, Gamping, Sleman, Indonesia. A set of questionnaires was given to the respondents to measure knowledge, attitude, perception, service access, and also peer's attitude to LGBT. Counseling was given once together with material content about LGBT awareness in family. Statistical analysis was employed to process and analyze the data. Results: The result showed factors correlated to stigma about LGBT on teenagers namely knowledge, attitude, perception, access to any service, and peer's attitude. The most influential factor was knowledge factor with p value 0.00 and peer's attitude with p value 0.02. Conclusion: After being participated in the study, it is expected that teenagers can give information to the family members, so the family members and the society will have appropriate knowledge and attitude related LGBT stigma. Received: 6 February 2018, Reviewed: 12 February 2018, Received in revised form: 16 June 2018, Accepted: 27 June 2018.